The melody of F.I.M : Proud to be a part of I.M, journey & experience / Errneta Abu Bakar - Abu Bakar, Errneta (Faculty of Information Management, 2015)
Everyone have their own story about their life whether during study or having a career where the experience that will never forget along their life. UiTM MERBOK, KEDAH and UiTM PUNCAK PERDANA is a different campus which provided Faculty Information Management (FIM) generally teach their student on how to manage the information since nowadays the world undergo information explosion, this course will pay close attention to everyone. Here are some experiences from three students of Faculty Information Management named Errneta Binti Abu Bakar, Anasuhana binti Mohd Zaki and Aminuddin bin Marsidi narrate their life from they started study at FIM since Diploma until Degree.